Two open states of P2X receptor channels - Rokic, Milos B.; Stojilkovic, Stanko S. (Frontiers in Cellular Neuroscience, 2013)
The occupancy of the orthosteric ligand binding sites of P2X receptor (P2XR) channels causes the rapid opening of a small cation-permeable pore, followed by a gradual dilation that renders the pore permeable to large organic cations. Electrophysiologically, this phenomenon was shown using whole-cell current recording on P2X2R-, P2X2/X5R-, P2X4R- and P2X7R-expressing cells that were bathed in N-methyl-D-glucamine (NMDG+)-containing buffers in the presence and/or absence of small monovalent and divalent cations. The pore dilation of P2X4R and P2X7R caused a secondary current growth, whereas that of P2X2R showed a sustained kinetic coupling of dilation and desensitization, leading to receptor channel closure. The pore size of the P2X7R open and dilated states was estimated to be approximately 0.85 nm and greater than 1 nm, respectively. The P2XR pore dilation was also observed in intact cells by measurement of fluorescent dye uptake/release, application of polyethylene glycols of different sizes, and atomic force microscopy. However, pore dilation was not observed at the single channel level. Structural data describing the dilated state are not available, and the relevance of orthosteric and allosteric ligand interactions to pore dilation was not studied.